BNP as a New Biomarker of Cardiac Thyroid Hormone Function - Wang, Kaihao; Ojamaa, Kaie; Samuels, Abigail; Gilani, Nimra; Zhang, Kuo; An, Shimin; Zhang, Youhua; Tang, Yi-Da; Askari, Bardia; Gerdes, Anthony Martin (Frontiers in Physiology, 2020)
Background Cardiac re-expression of fetal genes in patients with heart failure (HF) suggests the presence of low cardiac tissue thyroid hormone (TH) function. However, serum concentrations of T3 and T4 are often normal or subclinically low, necessitating an alternative serum biomarker for low cardiac TH function to guide treatment of these patients. The clinical literature suggests that serum Brain Natriuretic Peptide (BNP) levels are inversely associated with serum triiodo-L-thyronine (T3) levels. The objective of this study was to investigate BNP as a potential serum biomarker for TH function in the heart. Methods Two animal models of thyroid hormone deficiency: (1) 8-weeks of propyl thiouracil-induced hypothyroidism (Hypo) in adult female rats were subsequently treated with oral T3 (10 μg/kg/d) for 3, 6, or 14 days; (2) HF induced by coronary artery ligation (myocardial infarction, MI) in adult female rats was treated daily with low dose oral T3 (5 μg/kg/d) for 8 or 16 wks. Results Six days of T3 treatment of Hypo rats normalized most cardiac functional parameters. Serum levels of BNP increased 5-fold in Hypo rats, while T3 treatment normalized BNP by day 14, showing a significant inverse relationship between serum BNP and free or total T3 concentrations. Myocardial BNP mRNA was increased 2.5-fold in Hypo rats and its expression was decreased to normal values by 14 days of T3 treatment. Measurements of hemodynamic function showed significant dysfunction in MI rats after 16 weeks, with serum BNP increased by 4.5-fold and serum free and total T3 decreased significantly. Treatment with T3 decreased serum BNP while increasing total T3 indicating an inverse correlation between these two biologic factors (r2 = 0.676, p < 0.001). Myocardial BNP mRNA was increased 5-fold in MI rats which was significantly decreased by T3 over 8 to 16 week treatment periods. Conclusions Results from the two models of TH dysfunction confirmed an inverse relationship between tissue and serum T3 and BNP, such that the reduction in serum BNP could potentially be utilized to monitor efficacy and dosing of T3 treatment. Thus, serum BNP may serve as a reliable biomarker for cardiac TH function.